Entrando en cintura: implicaciones de política económica sobre la sostenibilidad de la deuda pública en la zona euro (2013)
The present article shows the theory implicit in the intertemporal government budget constraint. From this framework, it is run a series of simulation exercises about the public debt sustainability problem and the needed fiscal sacrifices to judge the actual level of sustainable indebtedness in some countries into Euro zone. Specifically, Greece, Portugal, Italy and Spain must generate a primary surplus of 44.1%, 10.5%, 6.8% and 4.5% of the GDP, respectively, to maintain their current amount of debt. On the other hand, Germany, France and the UK can have primary deficits due to their relation between growth rate and real interest rate.